BOOK ANALYSIS WITH THEMA GEOPOLITICS â€œMEDIA, TERRORISM AND THEORYâ€, A CRITICAL THEORY RESEARCH APPROACH USING SEMIOTIC ANALYSIS - Deddy Tobing; Henny Saptatia (Politeknik Negeri Media Kreatif, 2020)
This article seeks to create a discussion space related to the Media Book, Terrorism and Theory. This book seeks to provide an understanding of the contextualization of the global cycle of violence within the framework of